2002
DOI: 10.1021/jp025857s
|View full text |Cite
|
Sign up to set email alerts
|

Role of Structural Changes in the Triplet−Triplet Energy Transfer Process to Oxime Derivatives

Abstract: The triplet energy accepting properties of bridged hydroxy and methyl derivatives of acetophenone oxime were examined. Sandros and Agmon−Levine−Balzani (ALB) models were used to deduce the oxime triplet energies, , and the reorganizational intrinsic barriers, ΔG #(0), associated with the reaction. It is found for the first time that these compounds exhibit different degrees of nonvertical energy transfer (NVET) behavior, depending on their chemical structure. These structural properties have been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…However, it was previously found that a discrepancy between T 1 energy from experiments employing the Sandros equation (or extensions thereof) and the calculated adiabatic triplet energy can be as much as 25 %, depending on the structural flexibility of the triplet donor and acceptor. [21] In our studies no special care was taken to use only nonflexible sensitizers, so a measured T 1 energy 15 % higher than the calculated value is reasonable.…”
mentioning
confidence: 66%
“…However, it was previously found that a discrepancy between T 1 energy from experiments employing the Sandros equation (or extensions thereof) and the calculated adiabatic triplet energy can be as much as 25 %, depending on the structural flexibility of the triplet donor and acceptor. [21] In our studies no special care was taken to use only nonflexible sensitizers, so a measured T 1 energy 15 % higher than the calculated value is reasonable.…”
mentioning
confidence: 66%
“…Hence, the ketoxime intermediates are reported as either non-specific or are assumed to be in the sterically favoured anti-arrangement. Papers reporting exclusive syn-ketoxime formation [30][31][32][33] are spectroscopically indistinguishable from the anti-ketoxime 10, [34][35][36] adding a significant amount of uncertainty as far as the geometry is concerned. No paper identified the orientation of the oxime group for compounds 11-14.…”
Section: Resultsmentioning
confidence: 99%
“…Quenching of the ITX ketone triplet state (observed at 600 nm) by the silane in benzene occurs with a rate constant of 1 × 10 6 M −1 · s −1 and forms a silyl radical by a hydrogen transfer reaction as supported by the observation of the ketyl radical of ITX at 480 nm. Silyl radicals usually absorb in the UV range (300–330 nm) 14–16. As a consequence, the strong absorption of the ITX ketyl radical in this wavelength range prevents any direct observation of Si • in an ITX/silane system.…”
Section: Resultsmentioning
confidence: 99%
“…Silyl radicals can also be generated by an interaction between the silane and the t ‐butoxyl radical t ‐BuO • , this radical being formed14–16 by the photochemical decomposition of di‐ tert ‐butylperoxide. The hydrogen abstraction rate constant (5.5 × 10 7 M −1 · s −1 ) was determined by a classical Stern‐Volmer plot using the increasing time of the silyl radical as a function of the different silane concentrations.…”
Section: Resultsmentioning
confidence: 99%